Manifesting community language learning activities in Islamic boarding school speaking program - Bukhori, Bukhori; Irsyad, Muhammad (Englisia Journal, 2025)
Community Language Learning (CLL) is an educational approach designed to foster speaking proficiency. This study explores the application of CLL activities within an English-speaking program at an Islamic boarding school in Indragiri Hilir Regency, Riau. Employing a qualitative case study methodology, data were gathered through observations, interviews, and document analysis, involving four teachers and two students. Findings reveal that the CLL approach was implemented through four key activities: repetition, free conversation, listening practice, and daily speaking exercises, supported by media such as vocabulary boards (Richards & Rodgers, 2001). These activities significantly enhanced students’ speaking skills, fostering an interactive and collaborative learning environment. In conclusion, specific CLL activities proved effective for developing speaking proficiency in this Islamic boarding school context. Recommendations include addressing identified challenges to further optimize program effectiveness.